PENYALAHGUNAAN NAPZA (NARKOTIKA, PSIKOTROPIKA,DAN ZAT ADIKTIF) PADA REMAJA DI INDONESIA - Citra Kirana Astika Putri; Lina Rahmawati; Fary Ardian Syah; Refi Tri Wardani Rifai; Fathoni Yusuf (Repository UPNVJ, 2021)
One of the big problems facing Indonesia is the prevalence of drug abuse, especially those occurred in the teenagers. Drugs (Narcotics, Psychotropics, and other Addictive Substances) are substances which when entered into the human body will affect the body, especially the brain/central nervous system, causing physical, psychological, and social function disorders due to habit, addiction and dependence. against narcotics. Narcotics are divided into three groups. Psychotropic consists of four groups. While the addictive substances include alcohol, nicotine, and caffeine. Every substance that is part of the drug has harmful effects for its users either directly or indirectly. In addition, not only has an impact on physical health, but can also affect mental health. NAPZA abuse can be prevented by various ways, namely through information programs, educational programs, meaningful programming options, self-introduction programs and early interventions, as well as psychosocial skills programs. Keywords: Drugs, Narcotics, Psychotropics, Addictive Substances